Dziennik pisany noca, 1989-1992 - Herling-Grudzinski, Gustaw, 1919- (Warszawa : "Czytelnik", 1993)
Diaries of the Polish author covering 1989-1992.
Continues: Dziennik pisany noca, 1984-1988.
Includes bibliographical references (p. 383-[384]).
Keywords: Herling-Grudzinski, Gustaw, -- 1919- -- Diaries; Authors, Polish -- 20th century -- Diaries